2021
DOI: 10.1016/j.ebiom.2020.103137
|View full text |Cite
|
Sign up to set email alerts
|

Discordance of immunotherapy response predictive biomarkers between primary lesions and paired metastases in tumours: A systematic review and meta-analysis

Abstract: Background: Several biomarkers predict the efficacy of immunotherapy, which is essential for selecting patients who would potentially benefit. Discordant status of these biomarkers between primary tumours and paired metastases has been increasingly revealed. We aimed to comprehensively summarize the incidence of this phenomenon. Methods: Databases were searched to identify studies reporting primary-to-metastatic conversion of biomarkers, including programmed death ligand-1 (PD-L1), programmed cell death protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 106 publications
2
48
0
1
Order By: Relevance
“…The temporal evolution of the immune microenvironment, which transitions from equilibrium to escape as clinically overt metastatic disease becomes apparent, is well-described [41]. This phenomenon has been previously described by studies demonstrating low tumor infiltrating lymphocyte (TIL) counts at metastatic biopsies [40,42], which is expected considering that PD-L1 and TIL are moderately correlated [14,16,43]. In order to further corroborate the transition from an inflamed although suppressed microenvironment to an immune desert one [44], we identified five of the studies included in the present meta-analysis that also reported TIL data [14,23,32,33,37].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The temporal evolution of the immune microenvironment, which transitions from equilibrium to escape as clinically overt metastatic disease becomes apparent, is well-described [41]. This phenomenon has been previously described by studies demonstrating low tumor infiltrating lymphocyte (TIL) counts at metastatic biopsies [40,42], which is expected considering that PD-L1 and TIL are moderately correlated [14,16,43]. In order to further corroborate the transition from an inflamed although suppressed microenvironment to an immune desert one [44], we identified five of the studies included in the present meta-analysis that also reported TIL data [14,23,32,33,37].…”
Section: Discussionmentioning
confidence: 94%
“…This meta-analysis is the first, to the best of our knowledge, that provides not only data on PD-L1 positivity rates in primary and metastatic BC, discordance rates of matched tumors and directionality of discordance, but also, crucially due to its clinical utility for TNBC, separate information on expression in different cellular compartments. This was not explored in a previous meta-analysis that reported on discordance of multiple biomarkers, including PD-L1, across human cancers [40]. Exploratory analyses from IMPassion130 have suggested that there is discordance in PD-L1 status between primary tumor and metastasis, as well as greater relative benefit with checkpoint inhibition when PD-L1 is analyzed in the latter [14].…”
Section: Discussionmentioning
confidence: 99%
“…As aforementioned, the selection and the response to immunotherapy is based on several mechanisms that play different roles. ICs expression on tumor cells seems to be a necessary, but not sufficient information to to prove sufficient insights into immune mechanisms related to immunotherapy efficay, to select patients candidate to immunotherapy and to predict the reponse to treatment [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, new criteria for the selection of patients who could benefit from these therapies have been recently evaluated. In particular, the combined positive score (CPS) has been introduced, a composite of ICs (such as PD-L1) tumor proportion score (TPS) and host- and tumor-related parameters, which evaluates the percentage of positive ICs (tumor cells, lymphocytes and macrophages) present in the TME [ 43 , 44 ].…”
Section: Immunotherapies Targetsmentioning
confidence: 99%
“…Taking the gut microbiome as an example, its role in modulating adaptive immunity has been reported in CRC before ( 134 ). Moreover, the scholars found a high degree of discordance in primary and metastatic lesions of multiple biomarkers via a multidimensional analysis in 2020 ( 135 ). The discordance rate of PD-L1 (26%) and TIL (39%) between primary metastatic tumors were relatively higher than that in TMB (no significant difference) and MSI status (6%), indicating that the PD-L1expression and TIL are highly heterogeneous and likely to be disturbed by sampling sites.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%